Electrochemical Synthesis of 3,5-Bis(acyl)-1,2,4-thiadiazoles through n-Bu4NI-mediated Oxidative Dimerization of α-Oxothioamides - Mahadev SHIVARAJ; Rajaghatta N SURESH; Toreshettahally R SWAROOP; Manikyanahally N KUMARA; Kanchugarakoppal S RANGAPPA; Kempegowda MANTELINGU; Adaganahalli Boregowda MAMATHA DEVI; Madihalli Prasanna MANASA; Muddegowda UMASHANKARA (Electrochemistry, 2023)
An electrochemical synthesis of 3,5-bis(acyl)-1,2,4-thiadiazoles by the oxidative dimerization of α-oxothioamides with assistance of tetra-n-butylammonium iodide (TBAI) as electrolyte and mediator under constant current electrolysis (CCE) is reported. Herein, this approach is an example for S–N bond construction through the electrochemical method. Furthermore, the required intermediates α-oxothioamides are synthesized by the reaction of α-oxodithioesters with ammonium chloride in the presence of sodium acetate. The probable mechanism for the formation of final products is also presented. This strategy resulted in good to excellent yields of title compounds.